Procastrination Behavior In Class Xi High School Students In Man Y Makassar - Novita Maulidya Jalal (International Journal of Education, Vocational and Social Science, 2023)
Schools, with all their dynamics, require students to work on and complete assignments given by the teacher within the specified time duration. If students have difficulty carrying out assignments that have been assigned according to the specified time limit, often experience delays in submitting assignments, or are slow in regulating time in creating assignments, they can be said to be students who engage in academic procrastination. The aim of this research is to describe the academic procrastination behavior that occurs in class XI high school students at MAN Y Makassar. The research method used is a quantitative descriptive research method using percentage techniques. The subjects in this research were 46 Class XI high school students at MAN Y Makassar. The data collection technique used is a questionnaire (scale). Indicators of Academic Procrastination in this research are delays in starting and completing academic assignments, delays in doing academic assignments, time gaps between actual work plans in doing academic assignments and doing other activities that are more enjoyable than doing academic assignments. From the results of this research, the results obtained were that 43.2% of students stated that students delayed starting and completing their academic assignments, 50.8% of students stated that they were late in doing academic assignments, 46.9% of students stated that students experienced time gaps between actual work plans. in doing academic assignments, 42% of students stated that students did other activities that were more enjoyable than doing academic assignments. In conclusion, there were students who showed indicators of procastrinating behavior towards their academic assignments. The implication of this research is that it can be used by students or schools to make efforts to overcome academic procastrination behavior..